The costs of crime associated with stimulant use in a Canadian setting. (1st November 2017) - Enns, Benjamin; Krebs, Emanuel; DeBeck, Kora; Hayashi, Kanna; Milloy, M-J; Richardson, Lindsey; Wood, Evan; Nosyk, Bohdan
Highlights: Few studies have estimated the costs of crime associated with stimulant use. Substantial costs of crime associated with stimulant use. Results strengthen case for more research into treatments for stimulant use disorders. Abstract: Background: Costs attributable to criminal activity are a major component of the economic burden of substance use disorders, yet there is a paucity of empirical evidence on this topic. Our aim was to estimate the costs of crime associated with different forms and intensities of stimulant use. Methods: Retrospective cohort study, including individuals from three prospective cohorts in Vancouver, Canada, measured biannually (2011–2015), reporting stimulant use at baseline assessment. Monthly crime costs included policing, court, corrections, and criminal victimization (2016 CAD). We estimated monthly crime costs associated with mutually exclusive categories of crack, cocaine, methamphetamine, and polystimulant use, stratified by daily/non-daily use, relative to stimulant abstinence, as well as the independent effects of treatment (opioid agonist (OAT) and other addiction treatment). We used a two-part model, capturing the probability of criminal activity and costs of crime with generalized linear logistic and gamma regression models, respectively, controlling for age, gender, education, homelessness, mental health issues, employment, prior incarceration, alcohol and opioid use. Results: The study sample included 1599 individuals (median age 39, 65.9% male) assessed over 5299 biannual interviews. Estimates of associated monthly crime costs ranged from 5449 [95% C.I.: 2180, 8719] for non-daily polystimulant use, to 8893 [4196, 13, 589] for daily polystimulant use. Cost differences between daily/non-daily use, injection/non-injection, and stimulant type were not statistically significant. Drug treatment was not associated with lower monthly crime costs in our sample. Conclusions: Substantial crime-related costs were associated with stimulant use, emphasizing the urgency for development and implementation of efficacious treatment regimens.